2014
DOI: 10.1002/acp.3087
|View full text |Cite
|
Sign up to set email alerts
|

Interviewing High Value Detainees: Securing Cooperation and Disclosures

Abstract: Four types of coercive and noncoercive interview strategies (legalistic, physical, cognitive and social) used to facilitate disclosure by high value detainees were examined in an international sample of practitioners and detainees (N = 64). Predictive analyses confirmed that the accusatorial approach was positively correlated with physically coercive strategies (r s = .58) and negatively with forms of social persuasion (r s = À.31). In response to social strategies, detainees were more likely to disclose meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 46 publications
7
72
1
Order By: Relevance
“…Although definitions of rapport vary widely (e.g., Army Field Manual 2-22.3, 2006; Grahe & Bernieri, 1999;Kleinman, 2006;Tickle-Degnen & Rosenthal, 1990), it is commonly (and internationally) acknowledged to be fundamental to successful interviews (e.g., Fisher & Geiselman, 1992;Goodman-Delahunty, Martschuk, & Dhami, 2014;Gudjonsson, 2003;Redlich, Kelly, & Miller, 2014;St-Yves & Meissner, 2014). Rapport is assumed to include elements of mutual attention (indicated by good listening), coordination (the degree to which the conversation is "in-sync," which might be reflected in verbal or nonverbal mimicry and matching motivational frames), and positivity (a generally pleasant demeanour; Abbe & Brandon, 2012.…”
Section: But What About Rapport?mentioning
confidence: 99%
“…Although definitions of rapport vary widely (e.g., Army Field Manual 2-22.3, 2006; Grahe & Bernieri, 1999;Kleinman, 2006;Tickle-Degnen & Rosenthal, 1990), it is commonly (and internationally) acknowledged to be fundamental to successful interviews (e.g., Fisher & Geiselman, 1992;Goodman-Delahunty, Martschuk, & Dhami, 2014;Gudjonsson, 2003;Redlich, Kelly, & Miller, 2014;St-Yves & Meissner, 2014). Rapport is assumed to include elements of mutual attention (indicated by good listening), coordination (the degree to which the conversation is "in-sync," which might be reflected in verbal or nonverbal mimicry and matching motivational frames), and positivity (a generally pleasant demeanour; Abbe & Brandon, 2012.…”
Section: But What About Rapport?mentioning
confidence: 99%
“…Goodman-Delahunty, Martschuk, & Dhami (2014) propose classifying interrogation methods in legalistic, physical, cognitive and social strategies that can be either coercive or non-coercive (Table 2).…”
Section: From the Interrogator's Point Of Viewmentioning
confidence: 99%
“…In fact, there is evidence showing that non-coercive forms of interrogation are much more effective than coercion 3,4,5 . For example, Goodman-Delahunty and colleagues 3 interviewed 64 law enforcement practitioners and detainees from five different countries, who were involved in high-stakes cases, mainly in alleged acts of terrorism. They found that reported confessions and admissions of guilt were four times more likely when the interrogators adopted a respectful interview strategy that aimed at building rapport with the detainee.…”
mentioning
confidence: 99%